Adherence, satisfaction, and quality of life in Wilson disease patients after switching to trientine tetrahydrochloride: observational data from a dual cohort study - Medici, Valentina; Cazzagon, Nora; Battezzati, Pier M.; Crosignani, Andrea; Civolani, Alberto; Bonaiuto, Emanuela; D’Incà, Renata; Vargiu, Emanuela; Tedone, Fabio; Lopatriello, Stefania; Zuin, Massimo (Frontiers in Pharmacology, 2025)
BackgroundWilson disease (WD) is a rare genetic disorder requiring lifelong treatment. Adherence to therapy is thus of utmost importance. We aimed to assess the change in treatment adherence and satisfaction in adult patients with WD after transitioning to trientine tetrahydrochloride (TETA 4HCl), a first-of-its-kind investigation.MethodsObservational, Italian multicenter study of adult patients switched to TETA 4HCl by their treating physicians. Eligibility criteria included WD patients either already switched (up to a maximum of 9 months before enrolment; retrospective-prospective [RP] cohort) or about to be switched (within 3 months following enrolment; prospective [P] cohort). Adherence was assessed by pill counts, self-reported Morisky Medication Assessment Scale and 24-h urinary copper excretion (UCE) values within expected range. Patient reported Experiences and Satisfaction with Medications and health related quality of life questionnaires were completed at baseline (T0) and after 3 months (T1).Results25 patients were enrolled: 9 in the RP and 16 in the P cohort, with median (IQR) age and time since diagnosis was 43.0 [(30.0, 52.0)] years and 24.0 [(14.0, 30.0)] years respectively. At T0, 40% of patients self- reported adherence according to MMAS and 58.3% were considered adherent according to UCE values. At T1, values increased to 64% (for both MMAS and UCE). Pill count (T1) suggested that 64% could be considered adherent. On a ten-point Likert scale from −5 to +5, median (IQR) satisfaction score was 4.0 [(4.0, 5.0)]. All quality-of-life (QoL) domains improved between T0 and T1.ConclusionAdults with WD on maintenance therapy following a switch in therapy to TETA 4HCl some improvements in adherence, satisfaction and QoL were observed.